APPLICATION OF HYDROPHOBIC CEMENT SLURRIES «RAN-M» OF «RAMSINKS-2M» GROUP TO AVOID FLUID KICK (Academic journal Industrial Machine Building Civil Engineering, 2018)
Laboratory studies of cement slurry and cement stone is established that hydrophobic cement slurry «RAN-M» consists of NTPha additives for well cements PTC-1-100 and «Ramsinks-2M». In the laboratory confirmed the technical parameters of the newest hydrophobic cement slurries (mobility, density, separation, pumpability, etc.) according to the standard requirements in the respective devices. Done such works as: implementation of the selection of formulations of cement slurries with different rate of strength development for different temperature integrals.
Keywords: permeability; well; technical condition; cement; Water-repellent; behand column overflows